(untitled) (Journal of history, 2025)
The article is devoted to the systematization and analysis of research conducted at the archaeological sites of the Keles Valley, which spans a history of more than one hundred years. The methodological basis of the research was based on the principles of historicism and scientific objectivity. The first of them requires to take into account the historical context in the interpretation of any types of sources and at the same time allows to consider the subject of research in relation to the processes and phenomena that took place in archaeological science in the late XIX century - early XX century. The principle of scientific objectivity became the basis for the source and historiographical analysis of the attracting materials. The authors tentatively distinguish three periods in the study of these sites: the pre-revolutionary period, the Soviet period, and the modern stage. The first period is characterized by the recording and general description of the monuments. The second stage is marked by the first comprehensive studies using traditional archaeological methods. The third stage is defined by large-scale and systematic research, employing methods from the natural sciences. The scientific novelty is the use of new approaches to determine more precise dating of monuments, classify samples of material culture and study in more depth the features of the historical development of the region. As a result of the study, and based on the analysis of the works of 19th-century local historians and travelers, valuable information was collected regarding the region’s history, ethnic composition of the population, and toponymy. Contemporary archaeological investigations have made it possible to obtain data on the structure of the monuments, their chronology, as well as the material and spiritual culture of the ancient population.